Territorialização do ensino na pandemia: perda e retorno ao espaço escolar pelos estudantes da E.E. Professora Ernestina Loureiro Miranda, Itapetininga/SP - Duarte, Caroline Ponce (2023)
With the pandemic, schools had to restrict the use of their space, meeting health requirements and modifying students' socio-spatial relationships with teaching. From this, students from the São Paulo public network were relocated to remote teaching, through educational platforms and fulfilling a responsibility that until then was primarily the responsibility of school units. The most affected were public school students, according to studies that revealed the deepening of digital and socio-spatial inequalities in this public. It is in this current context, of school routine changed by the health crisis caused by the new corona virus, that this research was developed, analyzing the situation and perspectives of high school students, of how their educational experiences were during the pandemic, based on the loss of school territory. The place of analysis was the State School Professora Ernestina Loureiro Miranda, located in Vila Belo Horizonte, in the city of Itapetininga/SP. The main objective was to understand how the sociospatial management of students occurred in the pandemic due to their removal from school, the implementation of remote teaching and the return to school. The methodology used was qualitative research, based on document analysis, bibliographic review and interviews with 12 students from the Ernestina school; in addition to the application of a remote teaching evaluation questionnaire to students in the second and third years of high school. Comprising the period from 2020, from the suspension of classes until 2022, the year in which students returned to schools in person, coinciding with the implementation of the Programa de Escola Integral (PEI). In summary, the results showed students' dissatisfaction with remote teaching, a modality that contributed to the loss of students' bond with the school and teachers, a movement known as deterritorialization. In addition to the increase in school dropouts, due to the way teaching was implemented in the pandemic, and the PEI, which changed the schedule and time that students spend at school. The final considerations draw attention to the need for schools to be spaces consistent with the social reality of students, so that the number of dropouts decreases and low-income students can have access to quality school and education.